HISTOPATHOLOGICAL AND BIOCHEMICAL STUDYTO EFFECT OF CODEINE-PARACETAMOLIN SPRAGUE DAWLEY RATS - Adel J. Hussein; Aseel Kamel Hameed; S.K.Majeed (Basrah Journal of Veterinary Research)
This study performed in twenty four male Sprague Dawley rats for (90) days which divided randomly into four equal groups. Group (1): received normal saline daily. Group (2): received orally codeine-paracetamol(40/2500 mg / kg b.w) daily. Group (3): received orally codeine-paracetamol (80/5000 mg / kg b.w)daily. Group (4): received orally codeine- paracetamol (160 /10000 mg / kg b.w) daily. After end of day (90) of study all animals were sacrificed to do the histopathological and biochemical examinations. The statistical analysis results revealed the body weight effects of codeine-paracetamol toxicity a significant (P≤0.05) decreases of treated group after (90) days of treatment. The histopathological investigation of liver, kidney and brain of treated groups showed centrolobular necrosis, dilation of sinusoids, vaculation of hepatocytes and septal fibrosis of liver while kidney showed vaculation of mesengial cells of glomeruli, necrosis of proximal convoluted tubules and dilation of renal cortical tubules, also brain of treated group showed vaculation of neurons, these changes are appeared mild in group (2), moderated in group (3) and sever in group (4). The statistical analysis results of biochemical investigations of liver and kidney function tests showed a significant (P≤0.05) increases of levels of serum AST, ALT, ALP, bilirubin and creatinine respectively in all treated groups which these enzymes increased mildly in group (2), moderately in group (3) and severely in group (4).